MicroRNAs are key regulators controlling iNKT and regulatory T-cell development and function - Zhou, Li (Nature Publishing Group, 2011)
MicroRNAs (miRNAs) are an abundant class of evolutionarily conserved, small, non-coding RNAs that post-transcriptionally regulate expression of their target genes. Emerging evidence indicates that miRNAs are important regulators that control the development, differentiation and function of different immune cells. Both CD4(+)CD25(+)Foxp3(+) regulatory T (Treg) cells and invariant natural killer T (iNKT) cells are critical for immune homeostasis and play a pivotal role in the maintenance of self-tolerance and immunity. Here, we review the important roles of miRNAs in the development and function of iNKT and Treg cells.